Da terra ao inferno: uma viagem pelas narrativas de Almeida Garrett e António Lobo Antunes - Bertao, Lara Silva Perussi [UNIFESP] (2020)
This research has whose subjects of analysis Viagens na minha terra (1846) from Almeida Garrett and Conhecimento do inferno (1980) from António Lobo Antunes, and investigates, more specifically, on the journeys that organize both narratives, Lisbon to Santarém and Algarve to Apples' Beach, respectively. The investigation's objective is to grasp the symbolic dimension of the geographical journeys made by the characters as well as the way they seem to invoke other journeys, fictional and autobiographical, insofar they point to the author-narrators' love stories and literary activity, and historical-critical, as they propose a problematizing reading of nineteenth-century and post-colonial Portugal.